Perceptions of a Norwegian clubhouse among its members: A psychometric evaluation of a user satisfaction tool - Uhrmann, Lisa S. (International Journal of Psychosocial Rehabilitation, 2017)
Survey tools to assess user satisfaction have gained increased attention as meaningful sources of information for quality assurance and development of health care services. Several tools are developed, but these mostly refer to clinical settings and therefore address patients receiving treatment within these settings. This study aimed to investigate the psychometric properties of a survey instrument used to assess user satisfaction among members of a clubhouse and possibly to improve the instrument. Principal Components Analysis was used to assess the instrument’s factor structure, and Cronbach’s Alpha was used to assess internal consistency of the scale items. The results showed that the scales improved their psychometric properties if two items were removed from the tool, and that two different factor structures may be applied. In conclusion, the survey tool may serve as a means to assess clubhouse members’ satisfaction with various aspects of the clubhouse